A new species of the hermit crab genus Diogenes (Crustacea: Decapoda: Diogenidae) from the coast of KwaZulu-Natal, South Africa - Landschoff, Jannes; Rahayu, Dwi Listyo (Zootaxa, 2018)
A new diogenid hermit crab with bright-white chelae, Diogenes albimanus n. sp., is described and illustrated, based on a single ovigerous female collected from KwaZulu-Natal, South Africa. The new species is compared to morphologically similar species, in particular to D. holthuisi and D. dorotheae, from which it is distinguishable by the shape and armature of the telson; and also to the superficially-similar South African D. extricatus, from which it differs by having the unarmed dorsal margins of the propodi and meri of the pereopods, as opposed to being armed with rows of strong spines. The unusually white chelae are similar in colour to those of D. takedai, but the coloration of all other parts is different in these two species. High quality macro photographs, a high-resolution microCT (μCT) scan of the whole animal, and the reference to the repository of the molecular barcode of the new species are provided.